Pengembangan Media Pembelajaran Berbasis Website Pada Materi Dampak Sosial Informatika (Cyberbullying) di SMPN 17 Malang - Fariz Noor Azizi; Hakkun Elmunsyah; Mira Cempaka; Aprilya Nofanti Arifin; Arya Kumara Adji; Dwi Cahya Puspita; Eka Mahendra Bagaskara; Galih Gumelar Sudi Kartomo Pamungkas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education plays a crucial role in a country's development as it serves as a means to improve the quality of human resources. Technological advancements have driven significant changes in the field of education, including the use of digital devices as learning media. At SMPN 17 Malang, the teaching of the topic "Social Impact of Informatics (Cyberbullying)" is still dominated by conventional methods such as lectures and textbooks, which are less engaging and do not align with students' learning styles, which tend to be visual and kinesthetic. This has led to low student engagement and understanding of the material. This study aims to develop an interactive web-based learning media that is expected to enhance students' understanding of cyberbullying material and cater to their needs and characteristics. The study also evaluates the media's validity through expert review and assesses students' responses to its use. The results of this study are expected to make a meaningful contribution to improving the quality of learning and supporting the implementation of the Merdeka Curriculum through the integration of digital technology in schools.